Structure, Phase Composition of Supercooled Austenite, and Kinetics of Its Decomposition in Perlite Temperature Range of Chromium–Manganese Cast Iron - Kutsova, V.Z.; Kovzel, M.A.; Shvets, P.U.; Grebeneva, A.V.; Prutchykova, V.V. (Металлофизика и новейшие технологии, 2018)
The current paper studies the kinetics features of supercooled austenite decomposition in the pearlite temperature range (600–500°C) in chromium–manganese cast iron with the content of 2.2% carbon, 12.63% chromium, 5.7% manganese. The structure formation, phase composition, hardness as well as the distribution of elements between the phases and the structural constituents of the above-mentioned cast iron after isothermal soaking are investigated. The average size of secondary carbides after isothermal soaking is determined using JMicroVision v.1.2.7 free software. В работе рассмотрены особенности кинетики распада переохлаждённого аустенита в перлитной области температур (600–500°C) в хромомарганцевом чугуне с содержанием 2,2% углерода, 12,63% хрома и 5,7% марганца. Изучено структурообразование, фазовый состав, твёрдость, а также распределение элементов между фазами и структурными составляющими исследуемого чугуна после изотермических выдержек. C помощью бесплатного программного обеспечения JMicroVision v.1.2.7. определён средний диаметр вторичных карбидов после изотермических выдержек. У роботі розглянуто особливості кінетики розпаду переохолодженого аустеніту в перлітній області температур (600–500°C) у хромоманґановому чавуні, що містить 2,2% вуглецю, 12,63% хрому та 5,7% манґану. Вивчено структуроутворення, фазовий склад, твердість, а також розподіл елементів між фазами та структурними складовими чавуну, який досліджувався після ізотермічних витримок. За допомогою безкоштовного програмного забезпечення JMicroVision v.1.2.7. визначено середній діяметер вторинних карбідів після ізотермічних витримок.